"Development of digital elevation model for Okomu National Park, Nigeria" (2018)
The type of soil, fauna and flora species that are found in an environment is affected by the elevation characteristics of the land. However, the ability to provide techniques and model that will effectively explain the elevation patterns of protected areas will aid sustainable management of the forest and its resources. This study developed Digital Elevation Model (DEM) for Okomu National Park, Nigeria. Point coordinates (2,272) with their respective elevations were randomly obtained covering the entire study area. Interpolated natural neighbor algorithm of the Quantum Geographic Information System was used to generate Digital Elevation Model for the National Park from the elevation data. Topographic map was extracted from the DEM at an interval of 10 m from one another. It was observed that the elevation in the study area ranged from 19 m to 105 m with an average of 56.32 m above sea level. Hence, the parkland is regarded as a gentle slope. This study revealed that the study area is not prone to flood or runoff due to its gentle slope nature. Therefore, this study is recommended as baseline information for ecological management as well as guide in the development of conservation strategies for flora and fauna species in the study area.